Fibrin deposition in tissues from endotoxin-treated mice correlates with decreases in the expression of urokinase-type but not tissue-type plasminogen activator. - Yamamoto, K (1996)
The primary hypothesis of this report is that the formation and subsequent removal of fibrin in specific tissues during pathologic processes reflects temporal changes in the local expression of key procoagulant and fibrinolytic genes. To begin to test this hypothesis, we have used quantitative PCR assays and in situ hybridization analysis to examine the effects of endotoxin on the expression of specific genes in murine tissues, and to relate these changes to fibrin deposition/dissolution using immunohistochemical approaches. Endotoxin caused large increases in plasminogen activator inhibitor-1 mRNA and modest increases in tissue factor mRNA in most tissues examined. However, fibrin was only detected in the kidneys and adrenals of endotoxin-treated mice, and it was transient. Unexpectedly, changes in urokinase-type plasminogen activator mRNA but not tissue-type plasminogen activator mRNA correlated with fibrin deposition/dissolution in these tissues. Pretreatment of mice with the fibrinolytic inhibitor epsilon-aminocaproic acid before endotoxin increased both the number of fibrin-positive tissues and the duration of fibrin deposition in the kidneys and adrenals. These results suggest that the absence of fibrin in some tissues reflects ongoing local fibrinolysis, and that increases in plasminogen activator inhibitory and tissue fac- tor gene expression and decreases in urokinase-type plasminogen activator expression are necessary for tissue-specific fibrin deposition. Changes in tissue-type plasminogen activator gene expression do not appear to be essential for fibrin deposition/dissolution in this murine model of sepsis.